(untitled) (Texas Journal of Agriculture and Biological Sciences, 2024)
Goat production for milk and meat is an age old practice and goat is one of the first animals to be domesticated by men. In early biblical literature references are made regarding goat for milk, meat, hide and manure. Throughout the world goat is considered as ‘poor man’s cow’.